Role of Habenula in Social and Reproductive Behaviors in Fish: Comparison With Mammals - Ogawa, Satoshi; Parhar, Ishwar S. (Frontiers in Behavioral Neuroscience, 2022)
Social behaviours such as mating, parenting, fighting and avoiding are essential functions as a communication tool in social animals, and are critical for the survival of individuals and species. Ssocial behaviours are controlled by a complex circuitry that comprises several key social brain regions, which is called the social behaviour network (SBN). The SBN further integrates social information with external and internal factors to select appropriate behavioural responses to social circumstances, called social decision-making. The social decision-making network (SDMN) and SBN are structurally, neurochemically and functionally conserved in vertebrates. The social decision-making process is also closely influenced by emotional assessment. The habenula has recently been recognized as a crucial centre for emotion-associated adaptation behaviours. Here we review the potential role of the habenula in social function with a special emphasis on fish studies. Further, based on evolutional, molecular, morphological and behavioural perspectives, we discuss the crucial role of the habenula in the vertebrate SDMN.